2008
DOI: 10.1111/j.1365-2648.2008.04647.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Making the best of it’: Chinese women’s experiences of adjusting to breast cancer diagnosis and treatment

Abstract: Our findings have implications for healthcare professionals also in countries with Chinese migrants, and could be used as a basis for information and emotional and social support interventions as these can be effective in promoting adjustment to breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 29 publications
(62 reference statements)
13
53
1
2
Order By: Relevance
“…Por último, el tratamiento con quimioterapia afecta la vida de toda la familia, lo que también es señalado por otros autores quienes reconocen al cáncer como una enfermedad familiar en donde las preocupaciones de los pacientes son compartidas por el cónyuge y otros miembros de la familia generándose diferentes ajustes y cambios de roles al interior de esta (24,35,36).…”
Section: Discussionunclassified
“…Por último, el tratamiento con quimioterapia afecta la vida de toda la familia, lo que también es señalado por otros autores quienes reconocen al cáncer como una enfermedad familiar en donde las preocupaciones de los pacientes son compartidas por el cónyuge y otros miembros de la familia generándose diferentes ajustes y cambios de roles al interior de esta (24,35,36).…”
Section: Discussionunclassified
“…Many studies have been reported the emotional changes when a cancer diagnosis is confirmed (Ching et al, 2009;Fu et al, 2008). Fu et al (2008) reported that Chinese women with breast cancer tend to try "making the best of it" (p.155); they would typically face the reality, take an active part in the cancer treatment, and sustain an optimistic spirit.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al (2008) reported that Chinese women with breast cancer tend to try "making the best of it" (p.155); they would typically face the reality, take an active part in the cancer treatment, and sustain an optimistic spirit. Participants in our study also demonstrated similar pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these patients experience a sense of imminent death and being close to death, therefore, nowadays death anxiety is one of the main psychological factors among the patients with cancer. Even in types of cancers, which have an effective treatment, the patients consider a cancer diagnosis to be equivalent to death due to limited information regarding their disease (4). Despite the medical advances, development of cancer treatments, and also an increasing number of cancer survivors, this disorder causes severe affliction and deep fear in the individual.…”
Section: Dear Editormentioning
confidence: 99%